Transition of bioeconomy as a key concept for the agriculture and agribusiness development: An extensive review on ASEAN countries - Wang, Tiantian; Yu, Zhongkang; Ahmad, Riaz; Riaz, Samina; Khan, Kashif Ullah; Siyal, Saeed; Chaudhry, Muhammad Asif; Zhang, Taiming (Frontiers in Sustainable Food Systems, 2022)
Transition of bioeconomy plays an important role in the development of any economy. Therefore, the purpose of the current paper is to review the key concept of transition of the bioeconomy in the ASEAN economies that is considered to be an innovative collective method for observing the operation of national economies' numerous sectors that produce and process biological wealth. Based on current literature, it has been reviewed that the transition of bioeconomy is being presented with respect to the theoretical concept, and their essence and bioeconomy size, and the challenges and risks which are related to the bioeconomy transition. The various ways and the area of action along with present strategies which are supporting the development of bio economies and their relationship with the circular economies model had been presented. It was seen in the literature that ASEAN agricultures sectors had been contributing their major part in the development of value-added products and employment, except for Malaysia, Thailand, and Laos. Moreover, the analysis results had also shown that the transition of bioeconomy is considered to be an important concept in the growth of agriculture, forestry, agribusiness, and various sectors that produce and use bio-based raw materials. It was further found that for real bio-economy opportunities, it is essential that there should be a proper national and regional strategy for the bioeconomy development in place and for the development of a proper design and proper management coordination at every level of sectors, enterprises, and provincial systems.